More case studies in stroke: common and uncommon presentations - Hennerici, Michael G.; Kern, Rolf; Caplan, Louis R.; Szabo, Kristina (Cambridge University Press, 2014)
Stroke is the leading cause of permanent disability, including post-stroke dementia, pain, depression, and personality changes. While large clinical trials reflect information about large stroke populations, the presentation of each and every stroke patient is individual and special. More Case Studies in Stroke presents a new selection of stroke cases from seven countries prepared by practising stroke physicians. The book includes both common and unusual cases, as well as misleading cases of diseases mimicking stroke. The aim is to reinforce diagnostic skills through careful analysis of individual presenting patterns, and to guide treatment decisions. Each case consists of a clinical history, examination findings and special investigations, followed by diagnosis and discussion. The outline of the actual diagnostic process, including the use of modern diagnostic tools, decision making and course, challenge the reader at all stages of their career from medical students to neurologists and stroke physicians
Title from publisher's bibliographic system (viewed on 05 Oct 2015)